Representation of Woman Existentialist Reflected from Archetypal Image Analysis in The Chrysanthemums Story - Desria Natalia Sirait; Tomi Arianto (Institut Agama Islam Negeri Palopo, 2020)
This study aims at analyzing the representation of women's existence through the archetypal image in the chrysanthemum story. This study uses Carl Jung's archetypal image theory which is supported by Simone de Beauvoir's theoretical concepts. This research is focused on analyzing archetypal image. This story is revealed by classifying symbol, persona, anima and animus archetypal, and self-archetypal. Meanwhile, further analysis of the archetypal symbol is then criticized using the concept of the woman existentialist Simone de Beauvoir. This study uses a qualitative research method in which all data sources are taken from the short story. The results showed that there are four symbols of archetypal, personal archetypal, opposing points of view of anima and animus archetypal, and how to control self-archetypal. From all of these classifications, it is concluded that the representation of an existentialist woman is reflected through the main character named Elisa, including daring to go against the rules, being able to make their own decisions and being a woman who can stand alone.